Legal Protection For Business License Disputes Under Local Government Policy - Fahmi Nuraziz Awaludin; Ade Lukman Firmansyah; Azwa Khaliza; Distya Rahma Fauziah; Taufiq Alamsyah (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study examines the legal protection framework governing business licensing disputes arising from local government policies within the Indonesian administrative law system. The research employs a normative legal method based on doctrinal and conceptual approaches through the analysis of statutory regulations, legal principles, and administrative law doctrines. The study focuses on the interaction between local government authority, business licensing regulation, administrative disputes, and legal remedies available to affected parties. The findings indicate that the contemporary licensing regime seeks to promote investment efficiency through regulatory simplification and risk based governance while simultaneously generating legal challenges related to authority allocation, spatial planning compliance, environmental approval, administrative discretion, and public interest protection. The analysis further demonstrates that licensing disputes frequently emerge from inconsistencies between regulatory objectives and administrative implementation. Legal protection is provided through preventive and repressive mechanisms, including administrative objections, administrative appeals, and judicial review before the State Administrative Court. The effectiveness of these mechanisms depends on adherence to legality, accountability, proportionality, legal certainty, and the General Principles of Good Governance. Strengthening institutional coordination and enforcement capacity remains essential for ensuring fair and effective administrative justice in business licensing governance.